2017
DOI: 10.1177/2327857917061027
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing for Safety: A Human Factors-Influenced Procedure for Evaluating Medical Products

Abstract: Safety reports related to products and devices used in health care have demonstrated that not all items can be considered equal in terms of usability, compatibility, and functionality, which can result in patient safety concerns. Hospital systems use a wide variety of products when providing care to patients. This variability may contribute to purchasers failing to fully understand and define the needs for these products. In addition, it is necessary to define what a high-quality product is, including what min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Despite the mentioned recommendations, some data suggest that patient safety is not usually considered a relevant driver of healthcare technology procurement [30]. After detecting several safety incidents related to infusion pumps, the Healthcare Safety Investigation Branch [31] launched an investigation into the NHS to understand the emerging risks and barriers to the safe introduction of the technology and how data may help to demonstrate effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the mentioned recommendations, some data suggest that patient safety is not usually considered a relevant driver of healthcare technology procurement [30]. After detecting several safety incidents related to infusion pumps, the Healthcare Safety Investigation Branch [31] launched an investigation into the NHS to understand the emerging risks and barriers to the safe introduction of the technology and how data may help to demonstrate effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have been published about human factors evaluation, specifically of infusion pumps, related to the comparison of different equipment [34], for improving existing designs [11] or for supporting new designs [35,36]. However, human factors evaluation is not a usual practice as a supporting decision tool in medical technology in general [30]. Most medical technology procurement is driven by engineering standards, and the emphasis is on functional requirements rather than those relating to social or organizational needs [37].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the mentioned recommendations, some data suggest that patient safety is not usually considered as one relevant driver of healthcare technology procurement 30 . One investigation of the Healthcare Safety Investigation Branch 31 found that the procurement of smart pump technology is not primarily driven by the need for smart functionality and was not subjected to a risk assessment or requirements analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have been published in relation to human factors evaluation, speci cally of infusion pumps, related to the comparison of different equipment 34 , for improving existing designs 11 or for supporting new design 35,36 . However, human factors evaluation is not a usual practice as a supporting decision tool in medical technology in general 30 . In fact, most medical technology procurement is driven by engineering standards, and the emphasis is on functional requirements rather than those relating to social or organizational needs 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The Veterans Health Administration (VHA) has a duty to the Veteran patient, the provider, and the taxpayer. Previously, the authors described the "Purchasing for Safety Model," a method for medical device and product investigation prior to purchase (Fuller et al, 2017). This proactive method for assessing risk requires a substantial investment in terms of personnel time and expertise.…”
Section: Introductionmentioning
confidence: 99%